1996
DOI: 10.1136/jmg.33.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Familial adenomatous polyposis in a 5 year old child: a clinical, pathological, and molecular genetic study.

Abstract: A girl aged 5 years 8 months presented with rectal bleeding; her father had had familial adenomatous polyposis (FAP) and a colectomy at the age of 23. Endoscopy showed extensive polyposis and she had a colectomy. The proband and her father had the common codon 1309 5 bp deletion APC mutation. This mutation predisposes to early onset of FAP, and consideration needs to be given to having molecular testing of at risk members of these families done in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…The latter mutation, which accounts for about 20% of FAP pedigrees (Miyoshi et al, 1992a, 1992b, Varesco et al, 1993 and this study), tends to be associated with a very severe and early onset of the disease and CHRPE (Gayther et al, 1994). Distante et al (1996) reported a family in which a 5-year-old girl presented with rectal bleeding from extensive polyposis of the colon and her father had a colectomy for FAP at age 23 (Distante et al 1996). Accordingly, two of our unrelated patients with mutation 1309 had a very severe phenotype and a very early onset age, at 10 and 15 years, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…The latter mutation, which accounts for about 20% of FAP pedigrees (Miyoshi et al, 1992a, 1992b, Varesco et al, 1993 and this study), tends to be associated with a very severe and early onset of the disease and CHRPE (Gayther et al, 1994). Distante et al (1996) reported a family in which a 5-year-old girl presented with rectal bleeding from extensive polyposis of the colon and her father had a colectomy for FAP at age 23 (Distante et al 1996). Accordingly, two of our unrelated patients with mutation 1309 had a very severe phenotype and a very early onset age, at 10 and 15 years, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…Although the mean age for the development of colon cancer in patients with FAP is 39 years, there are reports of cases with colon cancer in children as young as 5 years old. 27 The lifetime risk for colorectal cancer is 100%, and adenomas can develop in other regions of the gastrointestinal tract (e.g., stomach and duodenum). In addition, these patients were also at a 1% risk of developing a hepatoblastoma during infancy and early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Two children had familial adenomatous polyposis (FAP), a hereditary defect that produces multiple polyps in the mucosa and that progresses to cancer. The muscle is not involved in the production of polyps and the colon is removed to prevent cancer development (Distante et al 1996;Gunther et al 2003). The entire colon was removed from two FAP children (8 and 12 years) and samples were collected from eight regions distributed along the colon of each child (Fig.…”
Section: Patients and Samplesmentioning
confidence: 99%